Anti-Bacterial activity of total flavonoids of Portulaca oleracea L. - Ramesh Londonkar; Hanumantappa B. Nayaka (International Journal of Phytomedicine, 2012)
Flavanoids are uniquitous in photosynthesizing cells and are commonly found in fruit, vegetables, nuts, seeds, stems, flowers and wine. For centuries, preparations canting these compounds as the principal, physiologically active constituents have been isolated and used to treat human diseases. Portuleca olerace L is an important medicinal plant that has been used in traditional medicine. The present study was aimed to isolate the total flovanoids and to investigate an anti-bacterial activity of total flavonids extracted from aerial part of Portulaca olerace L. we have used five standard pathogenic bacterial strains like Pseudomonas aeruginosa, Salmonella typhimurium, Proteus mirabilis, Klebsiella pneumonia and Enterobacter aerogenes, among all the bacterial strains Salmonella typhimurium (14.33±0.2886) and Proteus mirabilis (17.16±0.0281) have shown maximum zone of inhibition for total flovanoids and remaining bacterial strains have shown moderate zone of inhibition when compared with control (20.66±0.2881). In case of bio-assay method Salmonella typhimurium was shown more sensitive by low turbidity of OD value (0.187) indicating most significant result. The Minimum inhibitory Concentration (MIC) of the total flavonoids isolated from Portuleca olerace L was tested at the concentration ranging from undiluted sample to 10mg/ml. the minimum inhibition concentration (MIC) for the total flavonoids for all tested bacterial strains was >10mg/ml. Experimental results supports that these flavonoids have antibacterial properties which helps in the developing antibacterial agents in the form of drugs for the therapy of infectious diseases caused by these bacterial pathogens.